KNOWLEDGE AND PRACTICE OF RESTORING ENDODONTICALLY TREATED TEETH BY DENTISTS IN NORTHERN SAUDI ARABIA - Akbar, Iftikhar (European Scientific Journal, ESJ, 2014)
The aim of this study was to determine the knowledge, current approaches, techniques and practices for the restoration of endodontically treated teeth (ETT) among general dentists and specialists in northern Saudi Arabia. A standard questionnaire based survey containing 16 multiple choice questions about techniques and treatment methods, frequency of post, type of post, choice of luting cement, core material, reason for failure of endodontic treatment was distributed by hand and through email among 255 general dentists and specialists. The data was processed by using SPSS statistical software. The majority of clinicians (54%) believed that post reinforces the remaining tooth structure and reduces fracture probability. The ferrule effect was considered an important factor in increasing fracture resistance of the ETT (72%). The preferred technique for restoring ETT was core material along with 1-2 mm of ferule followed by prefabricated post and core build up. On the basis of post material, the most common was metal followed by fiber post. 2/3rd length of the root canal for the post length , 4-5mm apical seal of gutta percha after post placement and for the post diameter, 1/3rd of root diameter was agreed by most of the participants. Composite resin was the most popular material for core foundation followed by amalgam. The majority of surveyed practitioners had not a sound knowledge of the techniques and materials for restoring ETT and they believed that post reinforces the remaining tooth structure and reduces fracture probability.